Analisis Idiom Jawa dalam Cerkak ‘Kidung Tresna’ pada Majalah Panjebar Semangat Edisi 51 (DIWANGKARA: Jurnal Pendidikan Bahasa, Sastra dan Budaya Jawa, 2023)
Idioms are a form of cultural heritage in the language field. One of them is Javanese idiom. This study discusses the idioms contained in Javanese short story entitled ‘Kidung Tresna’ by Yustina Sri Warsiki. This research is in designed as qualitative descriptive. Data were collected through note taking technique and then analyzed by employing content analysis. Based on the results of the analysis, the researcher found five Javanese idioms contained in the Javanese short story, namely: paribasan (witing tresna jalaran saka kulina), saloka (Jaran Kerubuhan Empyak),tembung entar (abang raine), sanepa (ora ana banyu mili mendhuwur), and pepindhan (katon kaya cempaka sawakul).
Keywords: Language; Javanese Idiom; Javanese Short Story